Enhancing Elementary Students’ Reading Literacy through the Integration of the Reading Workshop Model and Self-Regulated Learning: A Systematic Literature Review - Rizkiah, Dimas; Sukartiningsih, Wahyu; Hendratno; Istiq'faroh, Nurul; Purwoko, Budi (Papanda Publisher, 2025)
This study aims to systematically examine the integration of the Reading Workshop model and the Self-Regulated Learning (SRL) approach in enhancing reading literacy among elementary school students. Utilizing the Systematic Literature Review (SLR) method, this research analyzed seven peer-reviewed articles published between 2019 and 2024 that focused on the development of reading literacy in primary education settings. The findings reveal that the Reading Workshop model, when combined with SRL strategies, significantly improves students' reading comprehension, autonomy, and motivation to read. This integrative approach supports students in setting reading goals, monitoring their comprehension, and reflecting on their reading practices. Additionally, the literature indicates that the incorporation of digital media, culturally responsive materials, and differentiated instruction further enhances literacy outcomes. Particularly, strategies such as Teaching at the Right Level (TaRL) enable teachers to tailor reading instruction to students’ actual reading levels, addressing diverse learning needs. In the context of the Merdeka Curriculum in Indonesia, which promotes personalized and inclusive education, the application of SRL-based Reading Workshop becomes highly relevant. Moreover, embedding local cultural values within reading materials fosters a deeper emotional connection and cultural awareness among students, enriching their overall literacy experience. The review concludes that an integrative literacy instruction model combining Reading Workshop and SRL, enriched by digital tools and contextualized content, is effective in addressing the challenges of reading literacy in elementary education. Future studies are encouraged to develop and empirically test instructional designs that operationalize this integration in classroom settings.